Causal association between gut microbiota and fibromyalgia: a Mendelian randomization study - Wang, Zhaohua; Jiang, Dan; Zhang, Min; Teng, Yu; Huang, Yaojiang (Frontiers in Microbiology, 2024)
Background: Fibromyalgia (FM) is a syndrome characterized by chronic and widespread musculoskeletal pain. A number of studies have implied a potential association between gut microbiota and FM. However, the casual association between gut microbiota and FM remains unknown. Method: Mendelian randomization (MR) study was conducted using the summary statistics of genetic variants from the genome-wide association study (GWAS). Inverse variance weighted (IVW), combined with MR-Egger and weighted median were used to investigate the causal association between 119 gut microbiota genera and FM. Sensitivity analyses were performed on the MR results, including heterogeneity test, Leave-one-out test and pleiotropy test. Results: A total of 1295 single nucleotide polymorphism (SNPs) were selected as instrumental variables (IVs), with no significant heterogeneity and pleiotropy according to the sensitivity analyses. Five gut microbiota genera were found to have significant casual association with FM. Coprococcus2 (OR = 2.317, P-value = 0.005，95% CI: 1.289-4.167) , Eggerthella (OR = 1.897, P-value = 0.001, 95% CI: 1.313-2.741) and Lactobacillus (OR = 1.576, P-value =0.020, 95% CI: 1.073-2.315) can increase the risk of FM. FamillyXIIIUCG001 (OR = 0.528, P-value = 0.038, 95% CI: 0.289-0.964) and Olsenella (OR = 0.747, P-value = 0.050, 95% CI: 0.557-1.000) can decrease the risk of FM. Conclusion: This MR study found that gut microbiota is casually associated with FM. New insights into the mechanisms of FM mediated by gut microbiota are provided.